Tanmiyah Al-MahÄrat Al-Lughawiyyah Li ThullÄb Kuliyyah Al-â€˜UlÅ«m Wa Al-TiknulÅ«jiya Min KhilÄl Al-Taâ€™lÄ«m FÄ« Al-HawÄi Al-Thalaq - Ningsih, Anita Andriya (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2021)
The process of learning Arabic at PKPBA takes a long time and the material is quite difficult for most students because they are Mubtadi (beginners) level, science and technology children, which is 30% of the number of UIN students who study Arabic with a myriad of mentoring activities, practicums, regular learning also all done in the classroom or room. The design in this study uses mixed methods with commensurate status and none is dominant between the two types of research. Qualitative research to determine the application of outbound in improving the Arabic language skills of students of the Faculty of Science and Technology of UIN Maulana Malik Ibrahim Malang and the use of quantitative methods to obtain an increase in the language skills of students of Science and Technology and the level of motivation of students of the Faculty of Science of UIN Maulana Malik Ibrahim Malang by implementing outbound in improving Arabic skills. The results showed that the games were grouped in each language skill. Among them, in special skills, you can play numbered chairs and chain whispers. In Kalam skills with guessing games, and reading skills by sorting words and writing skills by stringing letters into correct and meaningful words. Motivation to learn with the application of this outbound is very high from the results of the questionnaire. And the category of motivation is instrumental motivation because foreign languages are seen solely as a means of meeting practical needs (for example to get a good and steady job), not as a means of approaching other nations’ cultures.